Computational fluid dynamic investigations on effects of inserts in fast reactor fuel bundle hydraulics. (May 2019) - Padmakumar, G.; Velusamy, K.; Prasad, B.V.S.S.S.; Lijukrishnan, P.; Selvaraj, P.
Abstract: Hydraulic characteristics of a 7 pin helical spacer fast reactor fuel bundle have been investigated with focus on flow non-uniformity in the central and peripheral sub-channels. It is seen that, there is large variation in the flow distribution among the sub-channels with significant flow bypass in the peripheral sub-channels. To improve the flow uniformity, the option of providing inserts in the peripheral sub-channels has been investigated. In this direction, three types of inserts, viz., semi-circular, triangular and circular inserts, have been studied. The improvement in the flow distribution among the central and peripheral sub-channels and the increase in friction factor as a result of inserts have been quantified. The investigation is based on 3 dimensional computational fluid dynamic simulations as well as experiments in water models. In the experiments the flow pattern at the exit of fuel pin bundle has been measured using Particle Imaging Velocimetry. The pressure drop has been measured using differential pressure transmitter. The measured flow pattern and pressure drop in the bundle are compared with predicted results. The detailed parametric studies indicate that, among the three inserts studied the triangular insert provides lowest friction factor and largest axial velocity fraction in the central sub-channels. The circular inserts offer the maximum friction factor.